Johann Pachelbels geistliche Vokalmusik - Paech, Katharina Larissa (De musica disserenda, 2008)
Johann Pachelbel's sacred vocal music, especially his works composed for the specific needs of the Nuremberg liturgy, can be considered the apex of his compositional achievements. This paper discusses some background liturgical performance practice issues and analyzes the pieces from the point of view of their structure and style. The appendix contains a catalogue of Pachelbel's sacred works.
Keywords: Pachelbel, Johann, 1653-1706; music; glasba; 17.st.; duhovna vokalna glasba; Erfurt; Nürnberg; izvajalska praksa; katalog del